(untitled) (American Journal of Technology and Applied Sciences, 2024)
The article presents data on the speed and quantity of formation of a free crop structure when using organomineral fertilizers when caring for sunflowers and corn. At the same time, the most optimal results in the formation of sunflower and corn crop elements were achieved using combinations of the preparations Ecogum bio, Ecosil + Ecogum AF + Polybor and Ecosil + Ecogum complex + Ecogum FC + Polybor.